Trend of Non-Hodgkin Lymphoma Research Using a Genomics-Based Approach: A Bibliometric Analysis From 1985-2024 - Gustinanda, Rizky; Irham, Lalu Muhammad; Supadmi, Woro; Amukti, Danang Prasetyaning; Adikusuma, Wirawan; Chong, Rockie; Satria, Rahmat Dani; Khair, Riat El (Scripta Medica, 2025)
Non-Hodgkin lymphoma (NHL) is a group of malignant lymphoproliferative diseases that vary in histology, molecular biology, clinical presentation and prognosis. Genetic mutations and dysregulation play a critical role in its pathogenesis and classification. Understanding the publication landscape of NHL-related genetic studies is essential to map research trends and identify key contributors. This article aimed to conduct a bibliometric analysis of research trends in the field of Non-Hodgkin's Lymphoma and related genomic studies. This study used bibliometric analysis using Vosviewer 1.6.16 and Biblioshiny (R tool) to visualise and interpret global publication trends. Data were collected from the Scopus database using keywords related to "Non-Hodgkin's Lymphoma" and “Genomic”, covering publications from 1985 to 2024. The analysis identified that the United States dominates in citation contributions with a total of 7,328 citations, indicating strong research output and impact. The most productive journal was Blood with 57 publications, followed by Leukemia and the British Journal of Haematology. The most cited article was by Gaidano G (1991), published in PNAS, with a total of 906 citations. Co-authorship and keyword analysis revealed active international collaboration and emerging areas of focus such as BCL2, DLBCL and MYC. The trend in publications of NHL-related genetic research showed a significant increase over the years, with the US playing a dominant role in terms of output and citation impact. These findings highlight the growing interest and development in NHL genetic studies, which supports international collaboration and ongoing exploration of molecular targets.
Keywords: Lymphoma, non-Hodgkin; Genomics; Bibliometrics